Methods of testing refractory materials Part 5. Refractory and thermal properties Section 5.5 Determination of thermal conductivity ( panel / calorimeter method )( method 1902-505 ) (BSI, 1991)
Thermal measurement, Heat measurement, Refractories, Shaped refractories, Thermal testing, Refractory materials, Thermal conductivity, Test equipment, Testing conditions, Mathematical calculations, Dimensions, Test specimens, Circuits, Specimen preparation